Two Combustor Engine for Military Applications - Soon, Lee Aik (Cranfield University, 2009)
The key requirements for military aircraft are high survivability and mission success rate: the former will “exponentially” increase the latter. The survivability of the aircraft depends crucially on its performance and energy signatures, to which its propulsion system contributes significantly. Therefore this imposes demands upon future propulsion systems for a better aerothermodynamics performance with a lower energy signature. However, the performances achievable with conventional engine cycles may be reaching their limits. Therefore, the author was motivated to investigate the potential of the two combustor engine for military fighter applications; with respect to its aerothermodynamics performance and infrared signature. An extensive literature survey was conducted to identify the uptodate research for the two combustor engine. Based on the collected information, systematic approaches were formatted with proven analytical methodologies for conducting the present study. A proven conventional engine (i.e. F100PW229 engine, based on “open publication”), for powering military fighter aircraft, was selected for benchmarking purposes in order to identify the prospect of the two combustor engine. With an engine performance-simulation program of high fidelity and a detail engine model, the accuracy of the predictions of the engines’ performances are greatly improved. The key contribution is the establishment on the influences of the two combustor engine on the performances of the selected fighter aircraft, in particular the transient behaviour, steady state flight characteristics (e.g. flight envelope) and infrared signatures. This research relates the performance of the two combustor engine to that of the aircraft, which was not found in any uptodate publication. The availability of this research will allow engine and aircraft studies to include two combustor solution in a more secure way than it was possible. In this investigation, the main analytical tool employed is a Cranfield University inhouse developed engine performance-simulation program, TURBOMATCH. The author has implemented various subprograms to interface with TURBOMATCH in order to conduct specific simulations, e.g. transient behaviour predictions. All the analyses have been undertaken using data from the published literature.